Experiments and simulation of torque in Anton Paar powder cell. (19th May 2018) - Salehi, Hamid; Sofia, Daniele; Schütz, Denis; Barletta, Diego; Poletto, Massimo
ABSTRACT: Torque measurements were performed with the powder cell mounted on an Anton Parr rheometer using glass beads of two different sizes and different impeller geometries. A discrete element method simulator was used to perform simulations of the experiments to compare calculated torque values with those of the experimental torque values. Experimental torques obtained with flat two-blade impeller helped to find the correct sliding friction coefficient between beads. Experimental torques obtained with the circular impeller allowed to obtain the sliding friction coefficient between the impeller and beads. To estimate the wall friction coefficient, it was necessary to activate particle shear on the wall in configurations in which the gap between the impeller and wall is comparable with the bead size. It was verified that at the low shear rates used in this paper, the particle restitution coefficient is not significant and, therefore, higher impeller rotational velocities should be used to calibrate this parameter. Also, the differences between the torque values and time series of different impeller shapes were attributed to the different shearing surfaces and to the formation of instantaneous high magnitude force chains.